Age estimation in older adults: Use of pulp/tooth ratios calculated from tooth sections. Issue 3 (14th December 2017) - D'Ortenzio, Lori; Prowse, Tracy; Inskip, Michael; Kahlon, Bonnie; Brickley, Megan
Abstract: Objectives: Accurate age estimates are foundational for bioarchaeological research, yet the ability to accurately age older adult skeletons remains elusive. This study uses a new version of pulp/tooth area calculations to investigate chronological age of older archaeological individuals. Materials and Methods: Pulp/tooth area ratios were calculated on modern control teeth ( n  = 10) that were first radiographed and then sectioned for comparative analysis. Pulp/tooth area ratios were determined on sectioned teeth using ImageJ software for: (a) modern individuals of known age ( n  = 26); (b) individuals from Belleville, Ontario, Canada (1821–1874) with documented age ( n  = 50); and (c) Belleville individuals with skeletally estimated age ( n  = 122). Results: Calculations from tooth sections on modern teeth ( n  = 10) resulted in a mean absolute error (MAE) of ±3.9 years, whereas the radiographic method for the same teeth had an MAE of ±14.45 years. Results indicate that sectioned pulp/tooth area ratios are a significant predictor of chronological age ( p  < .005), with MAEs of ±4.53 years for Belleville and ±3.77 years for modern individuals. There were no statistically significant differences in age estimations between modern and archaeological individuals, or with respect to tooth type, sex, or intra/inter‐observer estimations. Discussion: This study provides a new more accurate method for estimating age‐at‐death, particularly for individuals in the 50+ age category. Sectioning the teeth and directly measuring exposed pulp chambers results in age estimations that were within ±4.15 years for both modern and archaeological individuals, thus presenting a method that will enhance the ability to age older individuals.